Economic benefits of combined open ditch and subsurface drainage based on the new calculation method considering both surface and subsurface waterlogging - Yuan Tao; Jing Liu; Xiaoyan Guan; Cui Zhou; Haorui Chen; Hejing Ren (Agricultural Water Management)
To better promote the combined surface and subsurface drainage combined drainage system, the economic benefit analysis is a crucial step. In flat plains and low-lying areas, it is difficult to remove all surface ponding solely through runoff. The subsurface drainage system is required to assist in the removal of surface ponding, especially where surface runoff is insufficiently low. However, in traditional designs, the effect of subsurface drainage on surface waterlogging removal is often neglected, as the system is usually designed to meet only subsurface waterlogging requirements. This paper proposes a new calculation method for the design of combined open ditch and subsurface drainage systems that considers both surface and subsurface waterlogging by introducing SDCSW parameter. The drain spacing and SDCSW obtained with HYDRUS are employed to verify the rationality of the proposed method. Then the economic benefits of the combined open ditch and subsurface drainage system were evaluated based on this new calculation method. The results indicate that the proposed method is feasible. Conventional subsurface drainage can remove approximately 15 % of surface ponding, while improved subsurface drainage with a 0.2 m-wide filter achieved removal rates of 19–23 %, provided drain spacing satisfied the subsurface waterlogging criterion. The ENPV of conventional subsurface drainage, improved subsurface drainage with a 0.2 m-wide filter, improved subsurface drainage with a 0.6 m-wide filter, and open ditch systems were 2315, 2186, 1635, and 1848 USD/ha, with corresponding economic benefit-cost ratios of 2.9, 2.6, 1.3, and 2.3 when drain depths were 0.8 m, respectively. At SDCSW = 0.8, the ENPV of the combined open ditch and improved subsurface drainage with a drain depth of 0.8 m and a 0.2 m-width filter, was 2231 USD/ha, representing 1.6 times that of the open ditch system but 2.6 % less than the combined open ditch and conventional subsurface drainage system (2293 USD/ha). The analysis also indicated that replacing gravel filter with straw in the improved subsurface drainage system would significantly increase ENPV. These findings contribute to advancing the design theory of combined open ditch and subsurface drainage systems and provide valuable references for their broader implementation and adoption.